PENGEMBANGAN KURSI ERGONOMIS DAN SENAM PEREGANGAN OTOT GUNA MENGURANGI KELUHAN OTOT RANGKA UMKM ROTI DI TOHUDAN COLOMADU - Widjanarti, Maria Paskanita; Suratna, Farhana Syarotun Nisa; Sumardiyono, Sumardiyono; Chahyadi , Bachtiar; Fauzi, Rachmawati Rrihantina; Wijayanti, Reni; Ada, Yeremia Rante (Jurnal Abdi Insani, 2025)
Occupational Health and Safety (OHS) programs in the informal sector of Micro, Small, and Medium Enterprises (MSMEs) remain limited. Informal workers in MSME bakeries are exposed to various physical, chemical, and ergonomic hazards, which contribute to health complaints. These complaints often manifest as pain and discomfort in the back, hands, and feet—common indicators of Musculoskeletal Disorders (MSDs). If left unaddressed, MSDs can adversely impact workers’ health, increase absenteeism, and ultimately reduce MSME productivity. This community service program involved several stages: an assessment of OHS conditions among service partners, the implementation of intervention activities, ongoing monitoring, and evaluation of outcomes. The initial assessment identified musculoskeletal complaints among partner workers. Interventions included work posture assessments, evaluation of MSD symptoms, body anthropometry measurements, the design and provision of ergonomic chairs, and the development of workplace stretching routines. Monitoring was conducted by observing changes in work posture following the ergonomic chair intervention, as well as tracking MSD complaints after the introduction of stretching exercises. Evaluation results showed a reduction in work posture risk, from level 4 to level 2, after the ergonomic chair intervention. Moreover, muscle stretching exercises helped reduce the intensity of MSD-related pain among informal workers.In conclusion, this community service initiative through the development of ergonomic seating and implementation of stretching exercises has contributed to a reduction in MSD complaints among informal bakery workers in Tohudan, Colomadu. These improvements are expected to enhance the overall productivity of the MSME sector.